Saffron growing in Uzbekistan and prospects for its development (Texas Journal of Agriculture and Biological Sciences, 2023)
Cultivation, breeding and establishment of industrial plantations of saffron and other promising medicinal plants in the soil and climate conditions of our Republic and the establishment of industrial plantations are not only used in the local pharmaceutical, food and perfumery, cosmetology industries, but also produce valuable products in the world market. creates an opportunity to export as